(3ajV GdbOjQ TQM GdLGeY GdUZjQs - (3GdMOGOj GdbGgQj GdefGhj, Rjf GdOjf, eMeO YHO GdQADa Hf JGL GdYGQajf Hf Ydj Hf Rjf GdYGHOjf, J (B1031 (3g`s ((3GdLGeY GdCehjs)
(3ChdgG (B:s
(3HYO GdHSedI ; hgPG MQa GdYjf (B((3YGjOI GdeQjV jeTj aj eNQaI GdLfI MJi jQLY(B) (3Cj jeTj aj GdJbGW ahGcg GdLfI hGdNQaI HGdVe eG jLJfi ef GdKeGQ hbO jJLhR HgG ddHSJGfs
(3BNQgG (B:s
(3hQhGg GHf eGLg Yf YHGOI Hf GdUGeJ HdaX eG ef eSde jSLO ddg SLOI EdG cJH Gddg dg HgG MSfI heMG Yfg SjFI hQaY HgG OQLI aCcKQhG GdSLhO GfJgi bGd GdMGaX GdYQGbj(B: (3hSfOg UMjMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 204s
(3eYLe GdeDdajf (B2 / 143s
(3cTa GdXfhf (B1 / 561s
(3GdHOQ GdWGdY (B1/ 357s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs